2017
DOI: 10.1016/j.socscimed.2017.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes towards alcohol control policies in Scotland and England: Results from a mixed-methods study

Abstract: The harmful effects of heavy drinking on health have been widely reported, yet public opinion on governmental responsibility for alcohol control remains divided. This study examines UK public attitudes towards alcohol policies, identifies underlying dimensions that inform these, and relationships with perceived effectiveness. A cross-sectional mixed methods study involving a telephone survey of 3477 adult drinkers aged 16–65 and sixteen focus groups with 89 adult drinkers in Scotland and England was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 31 publications
(46 reference statements)
11
49
0
Order By: Relevance
“…The magnitude of the associations were also consistent with previously published cross-sectional studies examining population-level effects and the association between increases in individual-level knowledge of the alcohol-cancer link and support for pricing policies observed in this study [36][37][38]. Other receiver characters associated with support for alcohol pricing, marketing, and availability policies in this study, such as being female, being of older age, having higher levels of education, and consuming lower levels of alcohol, are consistent with previous studies [35,37,[76][77][78][79]. Moreover, this study also observed, regardless of knowledge of the alcohol-cancer relationship, higher levels of support for alcohol marketing policies, relative to policies controlling the hours alcohol can be sold in off-premise retail outlets and the minimum unit price of alcohol, which are largely consistent with research from the US, Europe, and Australia [35][36][37][38]76].…”
Section: Discussionsupporting
confidence: 92%
“…The magnitude of the associations were also consistent with previously published cross-sectional studies examining population-level effects and the association between increases in individual-level knowledge of the alcohol-cancer link and support for pricing policies observed in this study [36][37][38]. Other receiver characters associated with support for alcohol pricing, marketing, and availability policies in this study, such as being female, being of older age, having higher levels of education, and consuming lower levels of alcohol, are consistent with previous studies [35,37,[76][77][78][79]. Moreover, this study also observed, regardless of knowledge of the alcohol-cancer relationship, higher levels of support for alcohol marketing policies, relative to policies controlling the hours alcohol can be sold in off-premise retail outlets and the minimum unit price of alcohol, which are largely consistent with research from the US, Europe, and Australia [35][36][37][38]76].…”
Section: Discussionsupporting
confidence: 92%
“…These positions related, as expected, with participants' demographic characteristics, the type of addictive behavior, and consumption habits. These findings are consistent with those of previous studies that showed that public opinion varied considerably towards leisure activity policies and that these views were associated with sociodemographic characteristics [26,35,36].…”
Section: Discussionsupporting
confidence: 93%
“…more police patrolling the streets) compared to policies restricting the availability of alcohol (e.g. increasing prices) [35,36]. This would therefore suggest, for example, that people are most concerned by the high-level of mortality caused by traffic accidents [35].…”
Section: Resultsmentioning
confidence: 99%
“…Despite this limitation, the overall sample size is comparable with similar studies of this nature. 26,29,30 Furthermore, the demographic profile of policy influencer respondents in our survey (eg, skewed toward older age and male) mirrors the demographic profile of policy leaders in Canada more generally. 31,32 Although we also had a relatively low response rate for members of the general public, participants were selected to mirror the demographic profiles found within each province.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 64%